2020
DOI: 10.1111/jace.17432
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationship amphoteric oxide systems via phase stability and ionic structural analysis

Abstract: Understanding the correlation between material deterioration and quality is required to control the slag composition with increasing gangue components (Al 2 O 3 /SiO 2) 1-3 and impurity elements (S and P). According to recent studies, 1,3,4 the flexibility of slag usage can be secured using the structure-property relationships of slag containing moderate CaO contents and amphoteric oxides such as Fe t O and Al 2 O 3. Detailed observations of the ionic structure of slags aid the fundamental understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…46) Recent studies showed that the activation energy was related to the polymeric unit (T-O-T, T = Si, Al, etc.). 47) With increasing Ce 2 O 3 addition from 5 wt% to 20 wt%, the apparent activation energy decreased from 168.44 ± 6.11 kJ•mol − 1 to 79.18 ± 2.59 kJ•mol − 1 , which indicated that the liquid shearing resistance of the slag reduced by the addition of Ce 2 O 3 content.…”
Section: Effect Of Ce 2 O 3 On the Viscositymentioning
confidence: 91%
“…46) Recent studies showed that the activation energy was related to the polymeric unit (T-O-T, T = Si, Al, etc.). 47) With increasing Ce 2 O 3 addition from 5 wt% to 20 wt%, the apparent activation energy decreased from 168.44 ± 6.11 kJ•mol − 1 to 79.18 ± 2.59 kJ•mol − 1 , which indicated that the liquid shearing resistance of the slag reduced by the addition of Ce 2 O 3 content.…”
Section: Effect Of Ce 2 O 3 On the Viscositymentioning
confidence: 91%
“…For example, the 10 wt% Al 2 O 3 sample did not adopt an acicular structure even at a cooling rate of 500 K/ min. This phase change is due to the rapid increase in the melt viscosity as the Al 2 O 3 content increases [31].…”
Section: Effects Of Al 2 O 3 Content On Microstructurementioning
confidence: 99%
“…13 The amphoteric oxide Al 2 O 3 can behave as a network modifier and also a network former, depending on the presence of other strong alkaline or acidic oxides. 14 High Al 2 O 3 content of high alumina slags leads to high viscosity and high melting point, which makes it difficult for the bosh slag to flow up and down in the furnace. 15 However, the structure of the depolymerized slag can be adjusted by adding appropriate MgO.…”
Section: Introductionmentioning
confidence: 99%
“…The metallurgical properties of the slag are determined by its composition and structure 13 . The amphoteric oxide Al 2 O 3 can behave as a network modifier and also a network former, depending on the presence of other strong alkaline or acidic oxides 14 . High Al 2 O 3 content of high alumina slags leads to high viscosity and high melting point, which makes it difficult for the bosh slag to flow up and down in the furnace 15 .…”
Section: Introductionmentioning
confidence: 99%